Analisa Tingkat Kebisingan Lalu Lintas Di Sekolah Dasar Katolik Santa Maria Pekanbaru: Analysis of Traffic Noise In Santa Maria Catholic Primary School Pekanbaru - Tarmizi, Tarmizi; Zaini, Abdul Kudus (JURNAL SAINTIS, 2015)
[ID] Kenyamanan akustik merupakan salah satu faktor penting dalam perancangan. Tujuan dari penelitian ini adalah untuk mengetahui tingkat kebisingan akibat lalu lintas pada ruas jalan Jenderal Ahmad Yani kawasan Sekolah Dasar Katolik Santa Maria, membandingkan tingkat kebisingan akibat lalu lintas dengan baku mutu tingkat kebisingan sesuai peruntukan kawasan/lingkungan serta memberikan solusi pengendalian/ penanganan kebisingan akibat lalu lintas. Metode yang digunakan untuk menganalisa tingkat kebisingan akibat lalu lintas mengadopsi pada model perhitungan tingkat kebisingan yang dikembangkan oleh Departmen of Transport United Kingdom yaitu Calculation of Road Traffic Noise (CoRTN). Secara umum pengukuran dengan alat ukur maupun persamaan empirik, telah melebihi baku tingkat yang diizinkan. Solusi penanganan/pengendalian kebisingan di lokasi penelitian dilakukan dengan membangun penghalang buatan antara jalan dan bangunan sekolah. Penghalang dari bahan susunan bata dengan tinggi 2,5 meter akan menghasilkan efektifitas reduksi sebesar 15 – 16 dBA dan material berat minimal 15 kg/m². Karena Jalan Ahmad Yani terdapat area Sekolah sebagaimana perlunya ketenangan proses belajar mengajar, maka perlunya membuat, mengatur dan penerapan ZoSS oleh Dinas terkait. [EN] Acoustic comfort is an important factor in the design. The purpose of this study was to determine the level of noise due to the traffic on the roads General Ahmad Yani region of Santa Maria Catholic Primary School, comparing the level of traffic noise due to the quality standards appropriate noise level allotment area / environment as well as providing control solutions / handling noise due to the cross.The method used to analyze the level of traffic noise due to adopt the noise level calculation model developed by the Department of Transport, United Kingdom namely Calculation of Road Traffic Noise (CoRTN). Because the value of the basic noise level calculation, prediction and measurement noise level SLM are not identical, then it should use the highest value. In general, the measurement of the measuring instrument or empirical equations, has exceeded the permissible level. Solution treatment / control noise in the study area by building an artificial barrier between the road and school buildings. Barrier of material brick structure with 2.5 meters high will result in effective reduction of 15-16 dBA and heavy material of at least 15 kg / m². Because there are areas of Jalan Ahmad Yani School as necessary peace of teaching and learning, the need to create, organize and ZoSS implementation by relevant agencies. Operating time is expressed by the board ZoSS additional traffic signs and limit the speed of the vehicle. The implementation of traffic lanes from two-way to one-way to divert the route of the vehicle.